Rapid Drop in Coronary Heart Disease Mortality in Czech Male Population-What Was Actually behind It? - Poledne, Rudolf; Kralova, Anna; Bartuskova, Hana; Paukner, Karel; Kauerova, Sona; Fronek, Jiri; Lanska, Vera; Kralova Lesna, Ivana (Biomedicines, 2022)
The high mortality of coronary heart disease (CHD) among Czech men-one of the highest worldwide-began to decline in 1991 soon after the abolition of government subsidies to all foodstuffs rich in animal fat. As participants in the WHO MONICA Project, we were able to analyze the CHD risk factors just before and after this major economic change. We had previously documented that the originally subsidized prices decreased animal fat consumption and consequently non-HDL cholesterol concentrations in the population. By the early 1990s, no progress had been made in the treatment of acute myocardial infarction, statins were unavailable as was not the currently more effective antihypertensive therapy. Our recent research proved a close relationship between cholesterolemia and proinflammatory macrophages in adipose tissue and accelerated macrophage polarization with increased palmitate and palmitoleate contents in cell membrane phospholipids. By contrast, the proportion of proinflammatory macrophages decreases with increasing presence of n-3 fatty acids in the cell membrane. The combination of non-HDL cholesterol drop and a decreased proportion of proinflammatory macrophages due to replacement of alimentary fat decreased CHD mortality immediately.
Keywords: inflammation; diet; macrophages; n-3 fatty acids; economy; coronary heart disease mortality; cholesterol